1996
DOI: 10.1021/jm950471+
|View full text |Cite
|
Sign up to set email alerts
|

Quinazoline Antifolate Thymidylate Synthase Inhibitors:  γ-Linked l-d, d-d, and d-l Dipeptide Analogues of 2-Desamino-2-methyl-N10-propargyl-5,8-dideazafolic Acid (ICI 198583),

Abstract: The syntheses of gamma-linked L-D, D-D, and D-L dipeptide analogues of 2-desamino-2-methyl-N10-propargyl-5,8-dideazafolic acid (ICI 198583) are described. The general methodology for the synthesis of these molecules involved the preparation of the dipeptide derivatives employing solution phase peptide synthesis followed by condensation of the dipeptide free bases with the appropriate pteroic acid analogue via diethyl cyanophosphoridate (DEPC) activation. In the final step, tert-butyl esters were removed by tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Our results show that caution must be used when interpreting the results of studies of the stereospecificity of FPGS, especially when one isomer has an especially low K m value. The occurrence of contaminating diastereomers of antifolate γ-dipeptides has been noted previously [34], but the biochemical consequences of these contaminants, especially with respect to FPGS activity, were not reported. Returning to the phosphinate-containing pseudopeptides, the two stereocenters of the final products were derived from, respectively, commercial L-glutamic acid to yield the 2S (L-) configuration at the N-terminal glutamate and a stereorandom synthesis of the C-terminal moiety.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results show that caution must be used when interpreting the results of studies of the stereospecificity of FPGS, especially when one isomer has an especially low K m value. The occurrence of contaminating diastereomers of antifolate γ-dipeptides has been noted previously [34], but the biochemical consequences of these contaminants, especially with respect to FPGS activity, were not reported. Returning to the phosphinate-containing pseudopeptides, the two stereocenters of the final products were derived from, respectively, commercial L-glutamic acid to yield the 2S (L-) configuration at the N-terminal glutamate and a stereorandom synthesis of the C-terminal moiety.…”
Section: Resultsmentioning
confidence: 96%
“…Current evidence suggests that FPGS is highly stereospecific for L-Glu (or close L-Glu structural analogs); this evidence is direct for the position occupied by the intrinsic Glu (position 1; [25, 32, 33]), but indirect for the first γ-Glu (position 2; [34]). Thus, the data of Table 1 were unexpected because the low R f species, which presumably mimic the unnatural L-Glu-γ-D-Glu configurations, remain highly potent FPGS inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, an L-Glu-γ-D-Glu dipeptide moiety replaces the glutamate moiety present in other antifolates. 33, 34 Further intracellular polyglutamylation of TS antifolate inhibitors by folate polyglutamate synthase increases their affinity for TS. 33,34 The L-Glu-γ-D-Glu dipeptide moiety of 1 serves the same purpose as the polyglutamate tail, increasing affinity for TS through electrostatic interactions with the positively charged polyglutamate-binding groove on the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…45,81,110 (b) Modifications to the glutamate portion of the molecule cause it to avoid the FPGS substrate activity but not the use of RFC to pass the cell membrane. [111][112][113][114][115] Two series of compounds have been designed starting from the structure of IC198583, conserving the quinazoline structure. 113 It was observed that modifications to the ␥-position of the glutamic acid residue in the dihydrofolate reductase inhibitor, MTX, resulted in compounds that are poor substrates or nonsubstrates for FPGS.…”
Section: B Antifolatesmentioning
confidence: 99%